Reservoir-Triggered Earthquakes Around the Atatürk Dam (Southeastern Turkey) - Büyükakpınar, Pınar; Cesca, Simone; Hainzl, Sebastian; Jamalreyhani, Mohammadreza; Heimann, Sebastian; Dahm, Torsten (Frontiers in Earth Science, 2021)
Reservoir-triggered seismicity has been observed near dams during construction, impoundment, and cyclic filling in many parts of the earth. In Turkey, the number of dams has increased substantially over the last decade, with Atatürk Dam being the largest dam in Turkey with a total water capacity of 48.7 billion m3. After the construction of the dam, the monitoring network has improved. Considering earthquakes above the long-term completeness magnitude of MC=3.5, the local seismicity rate has substantially increased after the filling of the reservoir. Recently, two damaging earthquakes of Mw 5.5 and Mw 5.1 occurred in the town of Samsat near the Atatürk Reservoir in 2017 and 2018, respectively. In this study, we analyze the spatio-temporal evolution of seismicity and its source properties in relation to the temporal water-level variations and the stresses resulting from surface loading and pore-pressure diffusion. We find that water-level and seismicity rate are anti-correlated, which is explained by the stabilization effect of the gravitational induced stress imposed by water loading on the local faults. On the other hand, we find that the overall effective stress in the seismogenic zone increased over decades due to pore-pressure diffusion, explaining the enhanced background seismicity during recent years. Additionally, we observe a progressive decrease of the Gutenberg-Richter b-value. Our results indicate that the stressing rate finally focused on the region where the two damaging earthquakes occurred in 2017 and 2018.